THE INFLUENCE OF COMPLEX TREATMENT WITH THE USE OF PHOTODYNAMIC THERAPY ON THE PERIODONTAL TISSUES’ CONDITION IN PATIENTS WITH GENERALIZED PERIODONTITIS - Личковська, О.Л.; Melnychuk, G. (World of Medicine and Biology, 2014)
The study involved 44 patients with chronic generalized periodontitis initial course, the first and second stage of progress, aged 20 to 44 years, without somatic pathology. In the adjuvant therapy photodynamic therapy diode laser „Granumˮ was used and in comparison, others had conventional treatment. It was found that, inclusion photoactivation desinfection in the classical scheme of treatment of patients with generalized periodontitis allows to increase the effectiveness of treatment with decresing side effects from the use of antiseptic and antibacterial agents.